OVUM PICK-UP- IN VITRO EMBRYO PRODUCTION - EMBRYO TRANSFER TECHNOLOGY IN THE APPLICATION OF WATER BUFFALO PRODUCTION - Guang-Sheng Qin; Ming-Tang Chen; Bing-ZhuangYang; Jia-xiang Huang; Chun-ying Pang; Xiu-fang Zhang; Xian-wei Liang; Zheng-zhun Tan; Hui Li; He-sheng Jiang (Journal of Animal and Plant Sciences, 2012)
The purpose of this study was to explore the feasibility of using ovum pick-up - in vitro embryo production and embryo transfer (OPU-IVEP-ET) in water buffalo production. As the water buffalo superovulatory responses and embryo transfer is inefficient in the past few years, there has been an increasing interest in the in vitro embryo production (IVEP) technologies for speeding up propagation of superior germplasm in buffaloes. OPU combined with IVEP can produce more embryos than MOET and which can improve the reproductive performance of water buffalo. At the same time, if combined with embryo cryopreservation and ET technology can speed up the breeding of water buffalo propagation and accelerate the development of dairy industry. In this study, well-bred frozen-thawed embryos were derived from OPU technology in the Laboratory of Guangxi Buffalo Research Institute. These types of embryos were transferred into the recipients in the Xiangbala Farm in Guilin. Two groups of crossbred water buffaloes were selected as recipients. One group with 11 heads was synchronized by injection PGc (0.6mg) intramuscularly. At the same time, another group of four animals in natural estrus were used. Frozen-thawed embryos were transferred at day 6 after estrous cycle. Results showed that there were 7 buffaloes observed to express estrus in the synchronization group with an estrus rate of 63.64%. Out of 7 buffalo recipients, 5 of them were transferred with embryos with the utilization rate of 71.43%. Pregnancy diagnosis was carried out to recipients at day 45 by B-mode ultrasound. Four recipients in natural estrus group were transferred with embryos. There were 3 recipients in the estrus synchronization group were found pregnant with the pregnancy rate of 60%, one recipient had a case of abortion while the two recipients delivered a healthy calf. On the other hand, the recipients in the natural estrus group were all found not pregnant. As indicated in this experiment, a total of 9 animals were transferred with embryos wherein 3 of the recipients were found pregnant. The pregnancy rate of frozen embryo obtained was 33.33% and two calves were born. Results suggested that OPU-IVEP-ET technology in water buffalo production was feasible and an effective way to speed up the propagation of water buffalo.
Keywords: Ovum pick-up; in vitro embryo production; embryo transfer; applications; Water buffalo